Economic Stabilization and Growth in Portugal - Schmitt, Hans (Occasional Papers; Occasional Paper ;, 1981)
This paper reviews economic stabilization and growth in Portugal during the 1970s. Following a decade of rapid growth with external equilibrium, the Portuguese economy in the early 1970s suffered a series of major shocks. The paper highlights that the problem of managing economic growth with a balance-of-payments constraint was new to Portugal. The paper reviews the issues that had to be resolved to develop an effective program. The economic outturn is also critically examined in this paper.